Fluid migration and hydrocarbon charge history of the vulcan sub-basin - Lisk, Mark (Curtin University, 2012)
A comprehensive examination of the hydrocarbon charge and formation water history of the central Vulcan Sub-basin, Timor Sea has been completed and a model developed to describe the evolution of the region’s petroleum systems. Reservoir horizons within the Mesozoic pre-, syn- and post-rift megasequences have been evaluated for their ability to host and retain oil and gas through a period of tectonic upheaval, associated with oblique plate collision in the Neogene. A coupled hydrocarbon-formation water model has been developed that describes two discrete formation water phases (W1 and W2) and three hydrocarbon phases (H1, H2, H3), with the timing of these events linked to important phases in the basin evolution.The Vulcan Sub-basin contains the components required to produce an effective petroleum system. The principal clastic reservoirs generally exhibit good porosity and permeability and are capped by effective, regionally extensive, seal rocks. A consistent paragenetic sequence can be recognised for Mesozoic reservoirs with early glauconite and pyrite phases preceding clay authigenesis. These early phases are in turn enclosed by quartz overgrowths that are subsequently enclosed by ankerite cement and in more deeply buried samples, filamentous illite. Source rocks are suitably located adjacent to these reservoirs, are organically rich and have experienced sufficient burial to promote thermal maturation and expulsion of generated hydrocarbons.The novel Grains with Oil Inclusions (GOI) fluid inclusion technique that allows the abundance of oil-filled fluid inclusions to be related to the maximum level of oil saturation experienced by a sandstone reservoir through time has been used to describe the charge history of a selection of wells from across the Vulcan Sub-basin. GOI data shows that the source rocks have been extremely productive, with three discernible hydrocarbon charge events recognised (H1, H2 and H3). An early gas charge (H1) appears to be widespread in the basin, but this may have been deleterious to regional prospectivity by reducing the volumetric capacity of traps that were well positioned to receive later oil charge.Stable isotope data from early formed clay and carbonate cements indicate connate waters extant during the first phase of hydrocarbon migration (H1) had mixed with meteoric water (W1) introduced into the reservoirs during periods of sub-aerial exposure associated with uplift related to rifting.A regionally extensive oil charge (H2), derived from Upper Jurassic mudstones, produced numerous, volumetrically significant, oil columns. GOI data shows that many of the current oil fields were once much larger and that many reservoirs that are now gas or water bearing also previously contained oil accumulations.Geochemical analysis of selected fluid inclusion oils (FIOs) show derivation from mixed marine and terrestrially derived source rocks of the Upper Jurassic Vulcan Formation. These oils form the first of two oil families that constitute the previously defined Jurassic Vulcan-Plover (!) petroleum system. In contrast the crude oils previously assigned to the second oil family and thought to have been derived from deltaic source rocks of the Middle Jurassic Plover Formation are not well represented in the FIOs. In addition a number of the FIOs are unlike either recognised oil family and show source rock characteristics that imply derivation from fully marine source rocks. These could represent either a previously unrecognised oil family or may reflect a true end member of the first family that has been mixed with the second family to produce an intermediate composition. The presence of the angiosperm marker Oleanane in some of the FIOs suggests a contribution from Cretaceous source rocks is also possible.The GOI data indicate high charge rates to structurally valid traps with at least one in three valid traps showing clear evidence of oil accumulation. Fluid inclusion palaeotemperature data, integrated with one dimensional (1D) basin models, produce a similar prediction of the charge timing with oil charge mostly from Eocene time. This agrees well with subsidence curves, which show a period of increased subsidence in the Paleocene that is likely to have promoted oil generation and expulsion into carrier beds used to facilitate oil migration into traps.Although an effective petroleum system can be demonstrated to have been present in the Tertiary, this has not been fully preserved due to events that post-dated hydrocarbon charge. The most significant of these has been the flexural bending of the lithospheric plate during oblique collision of the northwards moving Australian Plate with the eastwards moving S.E. Asian Plate. This collision produced a net extensional stress field throughout the Vulcan Sub-basin, resulting in widespread reactivation of deeper rift fault systems, and the formation of extensive arrays of shallow Miocene-Pliocene faults. Interaction between these fault populations has, in many cases, increased net-vertical structural permeability and led to breaching of hydrocarbon traps and the attendant leakage of oil and gas.Another major fluid-flow event that was controlled by the increase in structural permeability due to plate collision can also linked to the loss of hydrocarbons due to fault breach. A regionally extensive fluid-flow event, involving vertical, cross formation, migration of highly saline brine (W2) is indicated by fluid inclusion palaeo-salinity data. These palaeo-pore waters, with maximum salinities above 200,000 ppm NaCl equivalent, record the migration of high-salinity brines through Mesozoic and Tertiary sandstones. Fault controlled injection of brine from bedded salt at depths of up to 10 km is most likely the main source of this brine. Alternative salt sources in the drilled section are salt diapirs, but these are spatially restricted and their dissolution cannot reconcile the observed widespread distribution of these highly saline palaeo-fluids.In samples taken from intact hydrocarbon columns the absence of hyper-saline fluid inclusions suggests brine flow occurred after initial hydrocarbon charge. Further, high salinities seen in samples from recognised residual oil zones suggests that trap breach facilitated the ingress of high-salinity brines. Numerical simulations, utilised to test this hypothesis, produce outcomes that broadly match the observed distribution of samples with high salinity fluid inclusions.Brine flow from more deeply buried Palaeozoic strata also imparts a convective overprint on the conductive thermal background. Although not represented by the current geothermal conditions, thermal maturity data recording accumulated thermal stress, indicates localised heating of sediments immediately adjacent to faults bounding breached oil columns. The use of such anomalous maturity data when modelling hydrocarbon generation could lead to spurious conclusions if the restricted spatial extent of these convective effects is not considered.Aside from Neogene fault reactivation at least four additional processes have modified the preservation potential of the Jurassic Vulcan-Plover (!) petroleum system since the initial hydrocarbon charge. Although generally second order effects on a regional scale, these can be extremely important at the local scale. The first involves passive leak zones formed by reactivation of long-lived fault intersections that appear to control the trap capacity of the Skua oil field and likely play an important role more widely. Subsequent structural tilting during the Late Tertiary altered the spill-points of some hydrocarbon traps resulting in further redistribution of hydrocarbons. Demonstrable evidence of modification to spill-points after initial oil charge is recorded in the Skua Field where the original OWC is inclined, and can be explained by the establishment of north-westerly tilting.The third process to affect the system was a late stage gas charge (H3) that displaced oil from many of the traps that today contain gas. Considerable potential for downdip or displaced oil legs in the Swan and Oliver fields respectively is inferred.The final process to modify the petroleum system involved a significant increase in the magnitude of the horizontal stress component within the regional stress field, imparted by the jamming of the Banda Arc subduction zone by buoyant Australian Continental crust. The resultant reduction in observed extensional faulting likely led to an improvement in trap integrity such that heavily reactivated traps with access to charge could be successfully refilled.Data acquired by this study provides a base map of the charge history in the Vulcan Sub-basin with which to test the applicability of models proposed to predict the retention of hydrocarbons in yet to be drilled traps. These data already have been used to test models that utilise a variety of seepage detection methodologies including airborne and satellite based direct detection as well as indirect methods such as hydrocarbon related diagenesis. In the future, rigorous integration of these data into numerical models of fault reactivation that describe the complex interplay between stress, fluid-flow and regional tectonics will contribute to a better understand the mechanisms controlling fault breach in this region and in sedimentary basins elsewhere.